TRANSFORMATION OF REGIONAL FIRE SERVICES ORGANIZATION IN SERANG CITY BANTEN PROVINCE - Permana, Yogi Endra; Ilham, Muh.; Achmad, Mansyur; Tahir, M. Irwan (GoAcademica Research & Publishing, 2024)
Based on Law Number 23 of 2014 regarding on Regional Government, it is stated that fire is one of mandatory affairs relating to basic services in the field of public order and community protection. One of the consequences of mandatory matters related to basic services is the Minimum Service Standards (called SPM) set by the government to provide guarantees that all citizens in Indonesia will receive a minimum basic services, including in the fire sector. The institutional form of regional fire service organization is an important aspect in supporting the effective implementation of regional government duties in carrying out mandatory affairs related to basic services. Therefore, organizational transformation is a necessity that cannot be avoided, considering the various factors that influence the organization are changing so rapidly. The purpose of this research is to find out how organizational transformation occurs, to find the determining factors and to formulate a model for organizational transformation of regional fire service organization. The research method used is a descriptive method with a qualitative approach with data collection through interviews, observations and documentations. This research analyzes and evaluates the organizational structure of regional fire service organization in Serang City, Banten Province. The research results show that the transformation has been analyzed using the 4R approach (Reframing, Restructure, Revitalization and Renewal). In principle, the process of organizational transformation of regional fire service organization in Serang City, Banten Province has been carried out. This can be seen from the changes in organizational form and structure that adapt to district needs. However, this transformation shows suboptimal because it is not based on the implementation of the organization's mission, application of rules and political will. Thus, an ideal organization has not yet been achieved. A regional apparatus organization that handles the mandatory affairs related to basic services, the nomenclature, structure, duties and functions of fire and rescue services should be in an independent agency at least with the type C model.